Pengaruh Mindfulness Based Breathing Exercise terhadap Tingkat Burnout Syndrom Pada Perawat di Ruang Rawat Inap - Dilfa Simbala; Silvia Dewi Mayasari Riu; Norman Alfiat Talibo (CV. ALIM'SPUBLISHING, 2026)
Burnout syndrome is a condition characterized by emotional exhaustion, depersonalization, and a diminished sense of self-efficacy that nurses often experience due to high workloads. One approach that can be taken to reduce the level of burnout syndrome is through mindfulness-based breathing exercises. The objective of this study is to determine the effect of mindfulness-based breathing exercises on the level of burnout syndrome among nurses in the inpatient ward at R. W. Mongisidi Teling Hospital, a Type II General Hospital in Manado. This study employed a quasi-experimental design using a one-group pretest-posttest approach. The study population consisted of 87 nurses, with a sample of 20 respondents selected using purposive sampling. Data collection was conducted using the Mindfulness-Based Breathing Exercise SOP and a burnout questionnaire. The data were then analyzed using a T-test with a significance level (α) of 0.05. The study results showed that the mean score for the burnout syndrome among nurses in the inpatient ward of R. W. Mongisidi Type II General Hospital before the mindfulness-based breathing exercise intervention was 43.65, and the mean score after the intervention decreased to 40.40. The T-test results yielded a p-value of 0.000 < 0.05, indicating a significant effect of mindfulness-based breathing exercises on the burnout syndrome levels among nurses in the inpatient ward of RS TK II. R. W. Mongisidi in Teling, Manado. Mindfulness-based breathing exercises have a significant effect on burnout syndrome levels among nurses because this intervention helps improve self-awareness, control emotions, and reduce work-related stress. Recommendation: This intervention can be routinely implemented in hospitals as an effort to improve nurses’ psychological well-being and the quality of healthcare services.